Case Study Of ISO/TS16949 Application In Automotive Industry - Ahmad Rasdan, Ismail (2010)
In order to be able to compete in the marketplace, many industrial organization starts to equip themselves with quality standard such as ISO9001:2008, QS9000, ISO/TS16949 and ISO14001:2000. All this quality assurance systems are able to increase firms’ ability to compete, result in high quality products or services and increase social responsibility to workers. From the literature review, the authors found that the use of ISO/TS16949 standard in automotive industry is still at the early stage. Therefore, this gives an opportunity for the authors to conduct a case study to observe the effectiveness of ISO/TS16949 implementation in automotive supply chain. This study was conducted at three companies’ automotive component manufacturers in Malaysia. Having done that, comparison will be made based on similarities and differences between these companies. The result from this study shows that the main reason of applying this ISO/TS16949 standard was based on customer’s requirement. The main benefit of ISO/TS16949 implementation is reduction in rejection rate. Besides that, main obstacle in implementing ISO/TS16949 it is difficult to get full cooperation and acceptance from all staff in the organization. Therefore, it is important to understand the ISO/TS16949 implementation procedure in order to be successful in this high competitive globalise world.